Branding Sampah Anorganik Menjadi Karya Seni Yang Memiliki Nilai Jual - Ningrum, Ade Elisda Tiara; Mandira, I Made Chandra; Putra, I Gde Arya Yudana; Ningsih, Eka Putri Hayu; Aji, Wahyu Santoso; Anjani, Jihan Dwi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Penatahan Village is one of the villages in Tabanan Regency that has a bright future and, if properly managed, has the potential to become a one-of-a-kind destination for the wider community to visit. The purpose from this dedication is to bring understanding of Branding to the community, namely the younger generation of Penatahan village, in the hopes of making it easier for the community to realize the various potentials that exist in Penatahan village in the future. Mr. Made Bayak was interviewed via direct observation in order to acquire knowledge regarding plasticology branding, which was then implemented in the Penatahan village community with a sample of pupils from SMP Negeri 2 Penebel. The results acquired after providing material on how to brand, SMPN 2 Penebel students can basically comprehend how or the first step to launch a product using media platforms such as social media (Instagram).